2006
DOI: 10.1002/fld.1098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blockage on critical parameters for flow past a circular cylinder

Abstract: SUMMARYThe e ect of location of the lateral boundaries, of the computational domain, on the critical parameters for the instability of the ow past a circular cylinder is investigated. Linear stability analysis of the governing equations for incompressible ows is carried out via a stabilized ÿnite element method to predict the primary instability of the wake. The generalized eigenvalue problem resulting from the ÿnite element discretization of the equations is solved using a subspace iteration method to get the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…Details of the formulation for the LSA can be found in our earlier articles [7,9,12]. The non-linear equation system resulting from the finite element discretization of the flow equations is solved using the generalized minimal residual technique [13] in conjunction with diagonal preconditioners.…”
Section: The Finite Element Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the formulation for the LSA can be found in our earlier articles [7,9,12]. The non-linear equation system resulting from the finite element discretization of the flow equations is solved using the generalized minimal residual technique [13] in conjunction with diagonal preconditioners.…”
Section: The Finite Element Formulationmentioning
confidence: 99%
“…Various investigations, in the past, have shown that the LSA of the steady-state flow can provide a reasonably accurate estimate of the critical Reynolds number (Re c ) and the non-dimensional vortex shedding frequency (St c ) at the onset of the instability [3,[5][6][7]9]. In a recent study [9], it has been shown, via the LSA analysis, that to a large extent the blockage can explain the scatter in the data for the critical parameters at the onset of the instability, from various researchers in the past. The extrapolated values for a computational domain with an infinite lateral width are Re c = 47.380 and St c = 0.1163.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of numerical and experimental investigations have been conducted on the wake flows behind circular cylinders, as shown in the reviews by King [1], Sarpkaya [2,3], Bearman [4,5], Sumer and Fredsoe [6], Gabbai and Benaroya [7], Williamson and Govardhan [8,9], and Wu et al [10], Wu et al [11]. Alternating vortex shedding presents in the wake over a wide range of Reynolds numbers, resulting in structural vibration, acoustic noise, and significant increases in the drag and lift fluctuations [12][13][14][15]. This kind of fluctuations may cause fatigue in the structures and then sometimes lead to failure.…”
Section: Introductionmentioning
confidence: 97%
“…This specific Reynolds number is chosen because it is applicable to coastal marine structures, and this is also the upper bound that could be achieved in some laboratory measurements, thus the data are available to validate the numerical results. Besides the advection schemes and turbulence closure models, other factors such as the surface roughness of the cylinder (Szechenyi, 1975;Achenbach and Heinecke, 1981;Nakamura and Tomonari, 1982), the background turbulence intensity (Cheung and Melbourne, 1983;Kwok, 1986;Norberg and Sunden, 1987), and the distance between the cylinder and lateral boundary (Kumar and Mittal, 2006), could also influence the final results, which is not discussed in the present paper.…”
Section: Introductionmentioning
confidence: 80%